2018
DOI: 10.1017/s1366728918000500
|View full text |Cite
|
Sign up to set email alerts
|

Lexical selection, cross-language interaction, and switch costs in habitually codeswitching bilinguals

Abstract: Bilinguals dynamically activate lexical items in one or both languages depending on a number of factors. We explored the interaction effects of semantic constraints, language context, and L2-proficiency on cross-language interaction and switch costs in bilinguals who habitually codeswitch between Algerian Arabic (AA) and French. We recorded response times to French cognates and non-cognates embedded in auditory AA or French sentences. High proficiency bilinguals could restrict selection to the target language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 73 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Psycholinguistic and cognitive neuroscience studies on codeswitching have typically found that the comprehension and production of code-switches is costly (Costa & Santesteban, 2004;Meuter & Allport, 1999), but that this cost is modulated by participant characteristics, such as proficiency and language dominance (Bultena et al, 2015;Kheder & Kaan, 2019;Litcofsky & Van Hell, 2017), code-switching habits (Beatty-Martínez & Dussias, 2017;Kheder & Kaan, 2016;Valdés Kroff et al, 2020), frequency of switching patterns in the language (Guzzardo Tamargo et al, 2016), and social cues (Blanco-Elorrieta & Pylkkänen, 2017; Kaan et al, 2020;Martin et al, 2016). This suggests that code-switching is not necessarily costly, yet that its processing depends on how felicitous it is in a given context.…”
Section: Code-switchingmentioning
confidence: 99%
“…Psycholinguistic and cognitive neuroscience studies on codeswitching have typically found that the comprehension and production of code-switches is costly (Costa & Santesteban, 2004;Meuter & Allport, 1999), but that this cost is modulated by participant characteristics, such as proficiency and language dominance (Bultena et al, 2015;Kheder & Kaan, 2019;Litcofsky & Van Hell, 2017), code-switching habits (Beatty-Martínez & Dussias, 2017;Kheder & Kaan, 2016;Valdés Kroff et al, 2020), frequency of switching patterns in the language (Guzzardo Tamargo et al, 2016), and social cues (Blanco-Elorrieta & Pylkkänen, 2017; Kaan et al, 2020;Martin et al, 2016). This suggests that code-switching is not necessarily costly, yet that its processing depends on how felicitous it is in a given context.…”
Section: Code-switchingmentioning
confidence: 99%
“…Another important factor that has been shown to play a role in bilingual language processing and cognitive control is language proficiency (e.g., Declerck & Kormos, 2012; Kheder & Kaan, 2019; Pivneva, Palmer & Titone, 2012). In Mishra, Hilchey, Singh and Klein's (2012) study, proficient Hindi–English bilinguals were found to outperform bilingual peers with lower L2 proficiency level in a target detection task, reflecting the modulation effect of L2 proficiency on interference and attentional control.…”
Section: Introductionmentioning
confidence: 99%